Dividend policy in Nordic listed firms - Tor Brunzell; Eva Liljeblom; Anders Löflund; Mika Vaihekoski (Elsevier BV, 2022)
In this paper we analyze the results from a survey among all publicly listed Nordic firms on their dividend payout policy. The results show that 72% of the Nordic companies have a specified dividend policy. Larger and more profitable companies are more likely to have a defined dividend policy in place. The dividend policy is mostly influenced by capital structure considerations and the outlook of future earnings. We also find that the likelihood for a firm having an explicit dividend policy is positively related to ownership concentration as well as to the presence of large long-term private or industrial owners. Our results support the use of defined dividend policies for agency or monitoring reasons rather than signaling reasons.